ANALISIS MANAJEMEN KEGIATAN RUTIN SEKOLAH DI UPT SMP NEGERI 7 MEDAN - Efimah Sidabutar; Situmeang, Juwita; Odor Debora Pita Uli Sinaga (STKIP Subang, 2026)
This study examines the management of routine school activities at UPT SMP Negeri 7 Medan. The problem addressed in this research is the effectiveness of managing routine programs in supporting students’ character development and learning habits. The objective of this study is to describe the implementation of routine activities, analyze their management based on management functions, and identify their impact on students. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with teachers, and documentation studies. The results indicate that routine school activities have been implemented in a structured and consistent manner, including flag ceremonies, literacy programs, physical exercises, creative activities, and religious programs. These activities contribute positively to students’ discipline, responsibility, and participation. However, the implementation remains relatively uniform and has not fully accommodated students’ individual needs. In addition, the evaluation process is still descriptive and lacks measurable indicators. From a management perspective, the activities reflect the application of planning, organizing, actuating, and controlling functions, although the evaluation system has not been optimally structured. Therefore, improvements are needed in terms of differentiated activities, data-based evaluation, teacher involvement, and facility management to enhance the effectiveness of routine school programs.